THE JAPANESE ECONOMY AND THE COVID-19 PANDEMIC - Abe, Taro (Investigación Económica, 2021)
This study aims to elaborate on how the COVID-19 pandemic has affected Japan, particularly focusing on the country’s economic sector. In this study, we present the overall picture of the impact of the COVID-19 pandemic on Japan, focusing on why the country’s countermeasures against COVID-19 have been delayed. As per our findings, it would be safe to say that the Japanese government has failed to contain the COVID-19 pandemic by failing to provide sufficient medical support. This is because of its refusal to change from the conservative policies it has implemented since the 1990s. Half-hearted countermeasures against infectious diseases and economic promotion measures that are inconsistent with the countermeasures against infectious diseases have not slowed down the spread of the pandemic. A change in direction from conservatism is essential not only for the containment of the coronavirus but also for the prospect of a long-term sustainable society. LA ECONOMÍA JAPONESA Y LA PANDEMIA DE COVID-19 RESUMEN Este estudio tiene como objetivo explicar cómo ha afectado la pandemia de COVID-19 a Japón, enfocándonos especialmente en el sector económico del país. Presentamos el panorama general del impacto de la pandemia de COVID-19 en Japón, centrándonos en las razones por las que se han retrasado las contramedidas contra la pandemia. Según nuestras conclusiones, se puede afirmar que el gobierno japonés ha fracasado en la contención de la pandemia de COVID-19 al no proporcionar suficiente apoyo médico. Esto se debe a su negativa a cambiar las políticas conservadoras que ha aplicado desde la década de 1990. Las medidas poco entusiastas contra las enfermedades infecciosas y las políticas de promoción económica que no son coherentes con las estrategias contra las enfermedades infecciosas no han frenado la propagación de la enfermedad. Un cambio de rumbo de esas políticas es esencial no sólo para la contención del coronavirus, sino también para la perspectiva de una sociedad sostenible a largo plazo.